DESIGN AND IMPLEMENTATION OF FORTRAN-TERP INTERPRETER - Tjong Hui Tjhong; Triyono, MSC Triyono, MSC (Jurnal Sistem Komputer, 1992)
Development of an Interpreter called Portran-Terp. Fortran-Terp is bersifatrCompatible with Fortran programs written in means-Terp Fortran can be compiledwith a Fortran compiler without changes or with minimal changes.Development of an Interpreter requires good planning and structured. Each section /sub-systems in the implementation of an interpreter may be one or several ways.